Optimal design of velocity sensor for open channel flow using CFD - Dvorak, Joseph Scot; Zhang, Naiqian (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: In this study, computational fluid dynamics (CFD) was used to design the geometry of a new velocity sensor for measuring open channel flows. This sensor determined velocity by observing the travel of dye carried in the flow. Evaluation of this design required the development of fluid dynamics models to determine potential errors in fluid velocity measurement due to velocity changes caused by intrusion of the sensor in the fluid. It also required an analysis technique to determine the expected sensor response to the flow fields that resulted from the CFD modeling. These models were then used to improve the geometry of the sensor to minimize the measurement error. Starting with a simple design for the sensor geometry, the CFD analysis modeled the open channel flow around the sensor as turbulent using both the k-ω and k-ε Reynolds Averaged Navier-Stokes (RANS) turbulence models. The model predicted that the original sensor design would underestimate the free-stream velocities of open channels by 7.9% to 2.0% across a range from 0.1 m/s to 5.0 m/s. After using CFD to improve the sensor design, the velocity measurement error was limited to less than 4% across the same velocity range. Keywords: computational fluid dynamics, flow measurement, sensors, flow velocity, open channel DOI: 10.3965/j.ijabe.20171003.2147 Citation: Dvorak J S, Zhang N Q. Optimal design of velocity sensor for open channel flow using CFD. Int J Agric & Biol Eng, 2017; 10(3): 130–142.